Factors associated with unsafe sex behaviors for prevention of HIV/AIDS transmission among Myanmar migrant fishermen in Ranong, Thailand - K. Maler Htoo (Chulalongkorn University, 2012)
Thesis (M.P.H.)--Chulalongkorn University, 2008